Comparative Characterisation of Structural and Superconducting Properties of Y-123 and Y-247 Synthesised by Thermal Treatment at 980 °C - Yap, Siew Hong; Er, Tai Pao; Kechik, Mohd Mustafa Awang; Karim, Muhammad Khalis Abdul; Baqiah, Hussien; Chen, Soo Kien; Lim, Kean Pah; Shabdin, Muhammad Kashfi; Hapipi, Nurhidayah Mohd; Kamarudin, Aliah Nursyahirah; Mohamed, Arebat Ryad Alhadei; Doyan, Aris; Shaari, Abdul Halim (Balai Publikasi Indonesia, 2025)
This study presents a comparative analysis of the structural and superconducting properties of YBa₂Cu₃O₇−δ (Y-123) and Y₂Ba₄Cu₇O₁₅−δ (Y-247) superconductors synthesised via a thermal treatment method at 980 °C. Metal nitrates were used as starting precursors, with polyvinylpyrrolidone (PVP) serving as a capping agent to enhance dispersion and control microstructure. X-ray diffraction (XRD) confirmed that Y-123 and Y-247 were the dominant phases in their respective samples, although minor peaks of BaCuO₂ were detected, indicating the presence of secondary phases. Scanning electron microscopy (SEM) revealed that Y-247 exhibited larger grain morphology and higher porosity than Y-123, suggesting that the chosen sintering temperature exceeds the thermal stability range for the Y-247 phase. Electrical resistivity measurements showed a single superconducting transition for both samples, with Y-123 exhibiting a sharper transition width (ΔTc = 8.1 K) compared to Y-247, indicating better grain connectivity and phase uniformity. Energy dispersive X-ray spectroscopy (EDX) supported the elemental presence of Y, Ba, Cu, and O in both samples, though variations in stoichiometry were attributed to secondary phases. The observed expansion in the c-axis lattice of Y-247, combined with its higher porosity, points to oxygen loss during sintering, which contributes to the reduced superconducting performance. Overall, the results confirm that both Y-123 and Y-247 can be successfully synthesised using a simple and environmentally friendly thermal treatment method. However, Y-123 exhibits better structural integrity and superconducting performance at the high sintering temperature of 980 °C, making it a more promising candidate for large-scale production of bulk high-temperature superconductors.